With or against their region? Multiple-mandate holders in the Swiss parliament, 1985–2018. Issue 6 (2nd November 2021) - Freiburghaus, Rahel; Arens, Alexander; Mueller, Sean
ABSTRACT: Regional and local units try to influence national decision-making in various ways. This paper analyses one particular channel of subnational influence: multiple-mandate holders. These are members of the national Parliament (MPs) who at the same time hold an elected office at regional or local level. Focusing on Switzerland, we first assess the extent of this phenomenon over time and subnational space. We then test for its impact on MPs' actual vote choices, analyzing whether an MP's subnational loyalty outweighs party pressure on policy proposals submitted by a Swiss canton. Our analyses draw on a new, original dataset covering all ca. 1, 000 Swiss MPs between 1985 and 2018. In the main, we find that it is rather territorial homophily – the congruence of constituency and submitting canton – than holding dual mandates that plays a role when it comes to an individual MP's vote decision. However, territorial interests are indeed capable of outweighing partisan ties.